A Scheme for the Study of Discussions in the Social Media - Popping, Roel (Journal of Advances in Management Sciences & Information Systems, 2016)
In case one wants to study discussions in the social media one needs a template for doing this. The discussions can range from comments on some event to developing a deliberative democracy. This template, or scoring system, should give insight in developments in the substance of the discussion, but it should also allow considering the development of the structure of the discussion. In this text a template is proposed that covers both questions. The information that is collected by using the template might be useful in the context of (new) policy making; it can also be used to study opinions.